Consumption of omega-3 fatty acids and women's health - McManus, Alexandra; Newton, Wendy (OA Publishing London, 2013)
There is a substantial amount of evidence to support the role of long chain omega-3 fatty acids (n-3 LC-PUFAs) in the maintenance of optimal health and in the prevention of chronic disease. While many chronic conditions are not gender specific, there are emerging studies based on cohorts of women, specifically relevant to women’s health. Additionally, maternal and infant consumption of n-3 LC-PUFA as a part of a healthy and balanced diet can have lifelong effects on health outcomes. This review is a comprehensive look at research into the health benefits of n-3 LC-PUFA on women’s health. Research on female cohorts and that relating to issues specific to women’s health are reviewed. Research shows clear benefits to women’s health from consumption of the marine sourced n-3 LC-PUFAs. Evidence pertains to reductions in all-cause morbidity, coronary heart and cardiovascular disease, mental health including depression, dementia and Alzheimer’s disease, polycystic ovarian syndrome, dysmenorrhea and infant cognitive development.